Determination the Contact Stress Depending on the Load Rate of the NU220 Roller Bearing - Vasko, Milan; Guran, Ardeshir; Jakubovicova, Lenka; Kopas, Peter (Communications - Scientific Letters of the University of Zilina, 2013)
The purpose of this paper is to present the impact magnitude of the load rate of the roller bearing at mutual slewing of roller bearing rings to the process of contact stresses in rolling element. The roller bearing satisfies prescribed basic static load capacity if it is loaded by the maximum specified load only in the radial direction according to the ISO / TS 16281. The basic static radial load capacity of the cylindrical roller bearing determines the maximum loading for which there is no plastic deformation in the raceways yet. However, the real roller bearings are not loaded only in the radial direction in practice. During operation there exists a mutual slewing of the roller bearing rings. This leads to a change in the conditions of contact and contact stresses. The analysis of the mutual influence of these two parameters was made using finite-element software ADINA.
Keywords: roller bearing; rating life; contact mechanics; Hertz contact stress; FEM; computational analysis; stress analysis; ADINA